Evaluasi Pengelolaan dan Pemanfaatan Dana Desa pada Kampung Tanah Tinggi Distrik Malabotom Kabupaten Sorong Tahun 2018 - Frety Matahelumual; Wiesje Ferdinandus; Fadli Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to describe the management and utilization of Village Funds in physical development in Tanah Tiinggi Village, Malabotom District, Sorong Regency and identify supporting factors and inhibiting factors for the management and utilization of Village Funds in physical development in Tanah Tinggi Village, Malabotom District, Sorong Regency. The focus of this research is the management and utilization of the Village Fund which includes: planning, implementation, and accountability. This type of research is descriptive qualitative, the primary data sources in this study consist of key informants, namely the village head and village officials and community informants. Data collection techniques used three ways, namely observation, interviews and documentation. The data analysis technique used is an interactive model consisting of data collection, data condensation, data presentation and drawing conclusions. The results that can be concluded from this study are that the management of the Village Fund in physical development in Tanah Tinggi Village is in accordance with applicable regulations and is running quite well, but there are still some obstacles. The implementation of development is intended for the public interest in the form of construction of facilities and infrastructure. Accountability has been said to be good even though there are inhibiting factors from the Village Government, namely the lack of human resources and understanding of program planning.